PERATURAN DESA DAN KEDUDUKANNYA DALAM SISTEM HUKUM DI INDONESIA - Dwi Nur Kolipah; Muhyidin (The Republic : Journal of Constitutional Law, 2024)
As we know at the village government level, power is held by the Village Head together with village officials who are under the leadership of a Regent as the highest government authority at the Regency and/or Mayor at the City level. The implementation of village governance is also good in terms of development, the development of village communities must be based on Pancasila as the Staaffundamentalnorm, the 1945 Constitution, the concept of the Unitary State of the Republic of Indonesia and also Bhineka Tunggal Ika. Absolute guidelines for administering village administration are regulated in Article 2 of Law Number 6 of 2014 concerning Villages. running the government, holders of governmental power both at the center and in the regions have the authority to issue a policy related to discretion in their position. Even so, the policy must still be based on the applicable positive law. In forming government regulations, both central and regional must still be guided by the provisions in Law Number 12 of 2011 concerning the Formation of Legislation. In relation to village government, there is a form of regulation known as Village Regulation or Perdes. This is regulated in Article 26 of the Village Law as a juridical basis. However, Article 7 of Law Number 12 of 2011 does not find this form of regulation in the hierarchy of laws and regulations in Indonesia. Perdes is a form of government apparatus discretion at the village level, according to Freies Ermessen. Nevertheless, its implementation is not without limitations. The law is tasked with taking the role of preventing and anticipating arbitrariness.